Ordovician volcano–sedimentary iron deposits of the Eastern Tianshan area, Northwest China: the Tianhu example. Issue 11 (17th August 2016) - Wu, Chang-Zhi; Lei, Ru-Xiong; Santosh, M.; Chi, Guo-Xiang; Gu, Lian-Xing; Xie, Si-Wen
ABSTRACT: The stratabound Tianhu iron deposit, with a reserve of 104 Mt at 42% Fe, is located in the eastern part of the Central Tianshan zone in the southern part of the Central Asian Orogenic Belt. The deposit hosts schist, quartzite, marble, amphibolite, and granitic gneiss belonging to the Tianhu Group. Laser ablation inductively coupled plasma mass spectrometry was used to perform zircon U–Pb geochronology, bulk-rock geochemistry, and in situ zircon Hf isotope analyses of the metavolcanic host rocks for constraining the timing and genesis of the Tianhu iron deposit. According to the newly determined age constraints of 452 ± 3 and 477 ± 4 Ma, the iron deposit was concluded to be Ordovician in age. Geochemistry and zircon Lu–Hf isotope analyses suggested that the host rocks of the deposit represent metamorphosed arc-type volcanic rocks generated by the partial melting of a lower crustal source. Combined with geological and ore petrographic characteristics, the Tianhu iron deposit is interpreted to be of volcano–sedimentary origin with enrichment during subsequent metamorphism. The early Palaeozoic marks a critical iron mineralization epoch in the Eastern Tianshan area. The results also support the model of the Central Tianshan area as a volcanic-arc during the early Palaeozoic, associated with the subduction of the Northern Tianshan Ocean.